Patterns of acute poisoning for children during outbreak of Corona virus in Makkah region Saudi Arabia - Althobaiti, Bashayer Mohammed; El-Readi, Mahmoud Zaki; Althubiti, Mohammad; Alhindi, Yosra Zakariyya; Alzahrani, Abdullah R; Al-Ghamdi, Saeed S; Ayoub, Nahla; Refaat, Bassem; Eid, Safaa Yehia (Frontiers in Pediatrics, 2023)
Background: Poisoning occurs when someone is overexposed to a substance and  can reach children. Lungs, heart, CNS, digestive tract, and kidneys can be poisoned. Acute poisoning killed 45,000 children and teens in 2004, 13% of all accidental poisoning deaths worldwide. Exposure, age, poison, and dose affect poisoning patterns. This study examined acute drug, chemical, and natural toxin poisoning in children under 12. In 2020–2021, Haddah's forensic chemistry centre, Makkah registered the study. Methods: Makkah's 122 toxic-exposure children were studied retrospectively. The 12-year-olds were healthy for one year. Stratified random sampling divided cases into poison groups (pharmaceutical products, household products, plant envenomation, and animal envenomation). Each group received random samples. SPSS analysed data. Results: The mean age was 5.2 years, with 59% boys. The mean temperature, pulse, systolic, diastolic, and respiratory rates were 36.77, 98.29, 109.1, 69.17, and 21.49. Carbamazepine (5 mg), methanol, risperidone (5 mg), propranolol (5 mg), and olanzapine (5 mg) were the most documented pharmaceuticals (200 mg) (5 mg). Tablets (42.6%), syrups (15.6%), capsules (13.9%), and solutions (13.1%) were most common poisons. Ingestion (82.8%), dermal (5.7%), injection (4.9%), and inhalation (6.6%). 83% of children were poisoned accidentally, 30.3% within 30 minutes, and 69.7% at home. Benzodiazepines (18%) had normal pupils and an ECG of 85.2%. 67% had blood tests. The positive results were 213.01 and the sickness was 9.48. GIT and neurological symptoms (23.8%) predominated. 31.1% were toxic. 68% were complex. 34.4% of them had a breathing tube, 9.8% had repeated doses of activated charcoal to help them get rid of waste, and 27.8% were getting fluids through an IV. Children's severe toxicity was increased by GIT, CVS, respiratory, dermal, and neurological symptoms (p 0.05). Whole bowel irrigation, oxygen intubation, N-acetylcysteine, sedation, fluids, and phenytoin caused slight toxicity (P<0.05). Complications were associated with a higher mean AST (75.5 vs. 20.08, p<0.05). Toxicity was unrelated to lab test mean (p > 0.05). Children's systolic BP increased with age (r=0.22, p<0.01). The results show that the public needs to learn more about poisoning and that Saudi Arabia needs to set up ways to track poisonings and respond to them.